Estimation of isoniazid by digital image colorimetry: an integration of green chemistry and smartphone technology - Suvarna Yenduri; K. Naga Prashant (SpringerOpen, 2024)
Abstract Background This study proposes a simple digital image colorimetric method using a smartphone for the quantitative analysis of isoniazid in pharmaceutical medications. The analytical methodology employed in this study involved the utilization of the reaction between isoniazid and FC reagent under alkaline conditions. The chemical reaction led to the creation of a complex with a blue-gray color, exhibiting a peak absorption at a wavelength of 760 nm. An Android application was employed to perform a smartphone-based determination based on separating the captured color into different color channels such as red, blue, green, etc. The experimental procedure involved the utilization of three smartphones for the determination, which was subsequently followed by a comparative analysis of the results obtained from these devices using spectrophotometric measurements. Results The B channel had the highest level of optimization in terms of analytical parameters. The limits of detection (LOD) were 0.586, 2.478, and 1.396 µg/ml for S1, S2, and S3, respectively, and for the spectrophotometer, it was found to be 0.416 µg/ml. Similarly, LOQs were determined as 1.673, 7.511, 4.232, and 1.302 µg/ml. A %RSD of 1.3 for precision and an LOD of 0.013 g dm−3 were obtained for the spectroscopic method. The % recovery in the accuracy study was found to be 99.69, 101.804, 109.28, and 100.13 for S1, S2, S3, and spectrophotometer, respectively. Conclusion The colorimetric results from smartphone application are similar to those from spectrophotometric analyses.